Robotic radical hysterectomy for stage 1B1 cervical cancer: A case series of survival outcomes from a leading UK cancer centre. Issue 4 (7th May 2020) - Patel, Hersha; Madhuri, Kavitha; Rockell, Thomas; Montaser, Rugaia; Ellis, Patricia; Chatterjee, Jayanta; Butler‐Manuel, Simon; Tailor, Anil
Abstract: Background: We present the largest UK single institute robotic radical hysterectomy (RRH) case series for the management of cervical cancer (CC). Methods: Data were collected on women who had a RRH as primary treatment for stage 1b1 CC between December 2009 and December 2018. Results: Ninty women had a robotic hysterectomy. Five‐year follow‐up data were available for 30%. The disease‐free survival at 5 years was 89.6%. Overall survival at 3 and 5 years for death from any cause was 96.1% and 91.4%, respectively. The overall 5‐year survival for death from disease only was 92.8%. Overall survival by tumour size alone showed that women with tumours less than 2 cm had a 98.3% 5‐year survival compared to 83.4% for tumour size greater than 2 cm. Irrespective of tumour size, those that had no evidence of lymphovascular space invasion had a 100% 5‐year survival. Conclusion: Our preliminary data supports the oncological safety of RRH in a selective cohort of patients with stage 1b1 CC.